2020
DOI: 10.1111/apa.15705
|View full text |Cite
|
Sign up to set email alerts
|

Improving the uptake of Kangaroo Mother Care in neonatal units: A narrative review and conceptual framework

Abstract: Kangaroo Mother Care is a beneficial intervention for high‐risk infants; however, global uptake is lacking. Recent systematic reviews have collated the numerous studies that identify diverse barriers and enablers to the use of Kangaroo Mother Care. In this narrative review, we combine the findings of these systematic reviews with more recent studies to propose a conceptual framework, encompassing factors that may affect the initiation and maintenance of Kangaroo Mother Care in neonatal units. Conclusion This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…Despite its major benefits, KMC is not widely adopted in many LMICs. Inadequate facilities and/or space, limited hospital budgets, inadequate staffing, lack of KMC policies, and the reluctance of families to accept extended hospitalization are the main barriers to KMC uptake in Africa (16)(17)(18).…”
Section: Promoting Colonization With Normal Flora Kangaroo Mother Car...mentioning
confidence: 99%
“…Despite its major benefits, KMC is not widely adopted in many LMICs. Inadequate facilities and/or space, limited hospital budgets, inadequate staffing, lack of KMC policies, and the reluctance of families to accept extended hospitalization are the main barriers to KMC uptake in Africa (16)(17)(18).…”
Section: Promoting Colonization With Normal Flora Kangaroo Mother Car...mentioning
confidence: 99%
“…182,183 Studies report some barriers to use, but overall, skin-to-skin care is judged to be acceptable by both parents and caregivers. [184][185][186] Skin-to-skin care is likely to be cost-effective, acceptable, and feasible in high-, middle-, and low-income countries.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…Correspondingly, insufficient awareness of KMC and infant health among parents/family members was a barrier to the practice of KMC [ 22 ]. Despite the generally low awareness of KMC, the reviews reported that it was relatively easier to train mothers on KMC practices and that they were more adherent to KMC practices after understanding and accepting KMC [ 54 ]. Perceived, observed, and experienced effects of KMC could provide comfort and satisfaction to the parents of preterm infants, which promotes KMC use, whereas KMC is inhibited if parents and/or preterm infants experience KMC-related discomfort.…”
Section: Discussionmentioning
confidence: 99%